Reliability of U.S.D.A. beef carcass yield grades in reflecting differences in retail yields - Lipsey, R.J.; Allen, Dell M.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Retail cut-out and U.S.D.A. yield grade data were obtained on 1,121 carcasses of steers from Hereford and Angus dams mated artificially to Hereford, Angus, Jersey, Limousin, South Devon, Simmental and Charolais bulls. Calves were weaned when approximately 215 days old, conditioned 28 days, fed an average of 218 days after weaning before being slaughtered in a commercial slaughter plant. Carcass cooler data were obtained and the right side of each carcass was cut into closely trimmed, essentially boneless retail cuts at the KSU food service building. Beef yield grades do reflect definite differences in retail yields. Statistical tests indicated less than one chance in 1,000 that such differences occurred by chance and that the yield grade differences were real. The average difference in retail product percentage between yield grades was 4.6 percent. The average difference in fat trim percentage was 5.6 percent. For 700-pound carcasses, that's a difference of 39.2 pounds of waste fat, or 32.2 pounds of retail product. The difference in bone percentage would account for the other 7 pounds.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Yield grades; Retail yields; Product